High-Resolution Mass Spectrometer–Based Ultra-Deep Profile of Milk Whey Proteome in Indian Zebu (Sahiwal) Cattle - Chopra, Alka; Ali, Syed Azmal; Bathla, Shveta; Rawat, Preeti; Vohra, Vikas; Kumar, Sudarshan; Mohanty, Ashok Kumar (Frontiers in Nutrition, 2020)
Milk serves as a mode of protection to neonate through transferring the host defense proteins from mother to offspring. It also guards the mammary gland against various types of infections. Along with the presence of six vital proteins, bovine milk (whey) contains a massive class of minor proteins, not all of which have been comprehensively reported. In this study, we performed an LC-MS/MS-based ultra-deep identification of the milk whey proteome of Indian zebu (Sahiwal) cattle. Three independent search engines that are Comet, Tandem, and Mascot based analysis resulted in the discovery of over 6210 non-redundant proteins commonly identified. Genome-wise mapping revealed that Chromosome 1 showed a minimum expression of 14 proteins, while chromosome 19 expressing 250 maximum proteins in milk whey. These results demonstrate that milk proteome in Sahiwal cattle is quite complicated, and minor milk fractions play a significant role in host defense.